Biomaterials in Clinical Practice Advances in Clinical Research and Medical Devices - Zivic, Fatima; Affatato, Saverio; Trajanovic, Miroslav; Schnabelrauch, Matthias; Grujovic, Nenad; Choy, Kwang Leong; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book covers the properties of biomaterials that have found wide clinical applications, while also reviewing the state-of-the-art in the development towards future medical applications, starting with a brief introduction to the history of biomaterials used in hip arthroplasty.  The book then reviews general types of biomaterials - polymers, ceramics, and metals, as well as different material structures such as porous materials and coatings and their applications - before exploring various current research trends, such as biodegradable and porous metals, shape memory alloys, bioactive biomaterials and coatings, and nanometals used in the diagnosis and therapy of cancer.  In turn, the book discusses a range of methods and approaches used in connection with biomaterial properties and characterization - chemical properties, biocompatibility, in vivo behaviour characterisation, as well as genotoxicity and mutagenicity - an d reviews various diagnostic techniques: histopathological analysis, imagining techniques, and methods for physicochemical and spectroscopic characterization.  Properties of stent deployment procedures in cardiovascular surgeries, from aspects of prediction, development and deployment of stent geometries are presented on the basis of novel modelling approaches.  The last part of the book presents the clinical applications of biomaterials, together with case studies in dentistry, knee and hip prosthesis. Reflecting the efforts of a multidisciplinary team of authors, gathering chemical engineers, medical doctors, physicists and engineers, it presents a rich blend of perspectives on the application of biomaterials in clinical practice. The book will provide clinicians with an essential review of currently available solutions in specific medical areas, also incorporating non-medical solutions and standpoints, thus offering them a broader selection of materials and implantable solutions.   This work is the result of joint efforts of various academic and research institutions participating in WIMB Tempus project, 543898-TEMPUS-1-2013-1-ES-TEMPUS-JPHES, "Development of Sustainable Interrelations between Education, Research and Innovation at WBC Universities in Nanotechnologies and Advanced Materials where Innovation Means Business", co-funded by the Tempus Programme of the European Union.
Chapter 1. Short History of Biomaterials Used in Hip Arthroplasty and their Modern Evolution -- Part 1: Material Classes -- Chapter 2. Progress Beyond the State-of-the-art in the Field of Metallic Materials for Bioimplant Applications -- Chapter 4. Polymeric Biomaterials in Clinical Practice -- Chapter 5. Polymeric Biomaterials Based on Polylactide, Chitosan and Hydrogels in Medicine -- Chapter 6. Polyethylene Based Polymer for Joint Replacement -- Chapter 7. Ceramics for Hip Joint Replacement -- Chapter 8. Metallic Biomaterials -- Chapter 9. Biodegradable Metals as Biomaterials for Clinical Practice: Iron-based Materials -- Chapter 10. Porous Metals in Orthopaedics -- Chapter 11. Properties and Behavior of Shape Memory Alloys in the Scope of Biomedical and Engineering Applications -- Chapter 12. Bioactive Biomaterials: Potential for Application in Bone Regenerative Medicine -- Chapter 13. Bioactive Coatings -- Chapter 14. Nanometals in Cancer Diagnosis and Therapy -- Part 2: Biomaterial Properties and Characterization -- Chapter 15. Chemical Bulk Properties of Biomaterials -- Chapter 16. Assessment of Metallic Alloys Biocompatibility -- Chapter 17. Determining the Biological Properties of Biomaterials In Vivo -- Chapter 18. Genotoxicity and Mutagenicity Testing of Biomaterials -- Chapter 19. Histopathological Analysis of Bone Tissue Reaction on Implanted Biomaterials -- Chapter 20. Imaging in Clinical and Preclinical Practice -- Chapter 21. Selected Instrumental Methods for Physicochemical and Spectroscopic Characterization of Different Biomaterials -- Chapter 22. An Overview of In Vitro Mechanical and Structural Characterization of Hip Prosthesis Components -- Chapter 23. Characterization of Mechanical Properties of Metal Biomaterials -- Chapter 24. Manufacturability of Biomaterials -- Chapter 25. Computer Modeling of Stent Deployment in the Coronary Artery Coupled with Plaque Progression -- Part 3: Clinical Applications -- Chapter 26. Biomaterials in Dentistry - Implantology and Guided Bone Regeneration -- Chapter 27. Knee Arthroplasties -- Chapter 28. Total Endoprothesis of Hip Joint: Characteristics and Application in Patients in the Central Region of Serbia.
Keywords: Biomedical engineering; Biomaterials; Biotechnology; Medical care; Biomedical Engineering and Bioengineering; Biomaterials; Chemical Bioengineering; Health Care